Does the Impact of Education Expenditures on Economic Growth Vary Between Developed and Developing Countries? - Bayır, Musa; Zengin, Nazlıcan (Ekonomika, 2025)
Economic growth has been a fundamental policy objective for countries throughout history. It signifies an enhancement in a country’s well-being and income levels. Education also plays a significant role in economic development and welfare improvement. This study aims to empirically examine and compare the impact of education expenditure on economic growth in developed and developing countries. The research employs a panel Autoregressive Distributed Lag method to analyze the influence of education expenditures on national income in 20 developing and 27 developed countries over the period 2000–2020. The findings indicate that variations in education expenditure positively affect national income in both developed and developing countries, with a more pronounced impact observed in developed countries. Based on these results, it is inferred that the prioritization of education expenditures in economic policies is crucial for fostering economic growth.
Keywords: Education Expenditures; Economic growth; Developed and Developing Countries